Targeting Cellular Senescence with Liposome-Encapsulated Fisetin: Evidence of Senomorphic Effect - Henschke, Agata (2025)
Cellular senescence is closely connected with cancer progression, recurrence, and metastasis. Senotherapy aims to soothe the harmful effects of senescent cells either by inducing their apoptosis (senolytic) or by suppressing the senescence-associated secretory phenotype (SASP) (senomorphic). Fisetin, a well-studied senotherapeutic drug, was selected for this study to evaluate its efficiency when delivered in a liposomal formulation. The experiment evaluated the impact of liposome-encapsulated fisetin on senescent cells induced by doxorubicin (DOX) from two cell lines: WI-38 (normal lung fibroblasts) and A549 (lung carcinoma). Senescence was characterized by SA-β-galactosidase (SA-β-gal) activity, proliferation, morphology, and secretion of pro-inflammatory interleukin 6 (IL-6) and interleukin 8 (IL-8). Due to fisetin’s hydrophobic nature, it was encapsulated in liposomes to enhance cellular delivery. Cellular uptake studies confirmed that the liposomes were effectively internalized by both senescent cell types. Treatment with fisetin-loaded liposomes revealed a lack of senolytic effects but showed senomorphic activity, as evidenced by a significant reduction in IL-6 and IL-8 secretion in senescent cells. The liposomal formulation enhanced fisetin’s therapeutic efficacy, showing comparable results even at the lowest tested concentration.